SHOULD A FEDERAL TAX BAR BE ORGANIZED? - Seidman, J. S. (The Accounting Review, 1936)
Abstract The article discusses various issues related to the establishment of a federal tax bar in the U.S. Viewed from the narrow and introspective standpoint of the professions involved, there appear to he several avenues of utility. There is need for the better apprising taxpayers and the professions of the difference between the general practitioner and the tax practitioner. The field is also fertile for a more wholesome understanding all the way around of the separate boundaries and roles of the attorney and the accountant respectively. These functions may well be the province and product of an organization such as contemplated here. The organization may also take under its wing observations and recommendations on the rules of the game and having reached agreement from within, it could then present a coordinated viewpoint in the formulation or maintenance of correlative rules by external agencies, including the governmental departments and professional societies. Another possibility is the development of a central library for tax briefs akin to the libraries maintained in the general field by the larger bar associations, thereby affording practitioners the same advantage now enjoyed by the government staff in preliminary research for briefing on a particular tax subject.